Realization of Sustainable Development Goals with Disruptive Technologies by Integrating Industry 5.0, Society 5.0, Smart Cities and Villages - Kasinathan P.; Pugazhendhi R.; Elavarasan R.M.; Ramachandaramurthy V.K.; Ramanathan V.; Subramanian S.; Kumar S.; Nandhagopal K.; Raghavan R.R.V.; Rangasamy S.; Devendiran R.; Alsharif M.H. (MDPI, 2023)
business development; industrial technology; integrated approach; smart city; Sustainable Development Goal